New Normality policy under social philosophy scope - Montero Rodríguez, Jorge Luis (2021)
The current epidemic crisis has put into a hard spot the robustness of the contemporary social system based on politics, science, technology and free-market. The present text shows a critical observation to the current New Normality policy from a social-philosophical vision. This policy is a regression to certain governmental phenomena for gives it continuity and imposes certain social-moral behavior using a reinvented rhetoric. State-reformism, ethopolitics and resilience are notions to serve as arguments to support this thesis. At the end, I offer a purposeful discussion about subversion and antifragility of societies as a way of proposing a political strategy against a New Normality, because the New Normality is not a change, but a policy that promises a future time but not a different socioeconomic-political space.